2020
DOI: 10.3233/jpd-191890
|View full text |Cite
|
Sign up to set email alerts
|

Substantia Nigra Volume Dissociates Bradykinesia and Rigidity from Tremor in Parkinson’s Disease: A 7 Tesla Imaging Study

Abstract: Background: In postmortem analysis of late stage Parkinson's disease (PD) neuronal loss in the substantial nigra (SN) correlates with the antemortem severity of bradykinesia and rigidity, but not tremor. Objective: To investigate the relationship between midbrain nuclei volume as an in vivo biomarker for surviving neurons in mild-to-moderate patients using 7.0 Tesla MRI. Methods: We performed ultra-high resolution quantitative susceptibility mapping (QSM) on the midbrain in 32 PD participants with less than 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 85 publications
0
25
0
1
Order By: Relevance
“…Earlier clinicopathological studies have shown that the akinetic-rigid subtype exhibited more neuronal loss in the SN than the tremor-dominant subtype of PD (Paulus and Jellinger, 1991;Jellinger, 1999). A recent 7T MRI study confirmed this observation, showing that smaller SN areas correlated with higher bradykinesia-rigidity scores but not tremor scores (Poston et al, 2020). As we also observed a correlation between the SN area and the ordering-related caudate activation, it raises the question whether PD patients with less severe bradykinesia and rigidity would show greater ordering-related caudate activation and better sequencing performance.…”
Section: Limitations and Open Questionsmentioning
confidence: 82%
“…Earlier clinicopathological studies have shown that the akinetic-rigid subtype exhibited more neuronal loss in the SN than the tremor-dominant subtype of PD (Paulus and Jellinger, 1991;Jellinger, 1999). A recent 7T MRI study confirmed this observation, showing that smaller SN areas correlated with higher bradykinesia-rigidity scores but not tremor scores (Poston et al, 2020). As we also observed a correlation between the SN area and the ordering-related caudate activation, it raises the question whether PD patients with less severe bradykinesia and rigidity would show greater ordering-related caudate activation and better sequencing performance.…”
Section: Limitations and Open Questionsmentioning
confidence: 82%
“…In recent years, radiomics has been widely used in the field of oncology as an emerging discipline to predict treatment responses and survival outcomes for different cancers. 11 Radiomics is also used in PD, but most of this work constrains usable information to specific brain regions, such as the substantia nigra, 12 or uses other imaging modalities, such as neuromelanin imaging or DTI. 13,14 However, when considering the prevalence of PD and the need for cost-effective and relatively easy-to-use technologies, the applicability of these techniques may be limited.…”
Section: Introductionmentioning
confidence: 99%
“…Another well‐known neurodegenerative disease, PD, is described by tremor, rigidity, and bradykinesia in concomitant with postural shakiness looking in some patients since the disease advancements (Poston et al., 2020). It is pathologically identified through the loss of nigrostriatal dopaminergic innervation, while the neurodegeneration is recognized in both dopaminergic neurons and cells situated in other districts of the neural network (Li et al., 2020).…”
Section: Neurodegenerative Disease Pathologymentioning
confidence: 99%